2013
DOI: 10.1002/cncr.28032
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and relative survival of chordomas

Abstract: BACKGROUND: Chordomas are rare bone tumors arising from remnants of the embryonic notochord. METHODS: Data for this study were obtained from the Surveillance, Epidemiology, and End Results (SEER) Program of the National Cancer Institute to calculate the incidence, relative survival (RS), and standardized mortality ratio (SMR) of patients diagnosed with intracranial and extracranial chordomas and to assess the effects of age and sex on this disease. RESULTS: The overall incidence of extracranial and intracrani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
78
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(80 citation statements)
references
References 47 publications
2
78
0
Order By: Relevance
“…The overall age-specific incidence patterns reported in this study were consistent with those reported in Western countries,2,3,1220 showing that OS and ES are more likely to be diagnosed in youth, whereas CS and GCT occur more frequently in middle-aged and elderly individuals, and chordomas and ameloblastomas predominantly affect elderly patients. However, more details remain to be clarified.…”
Section: Discussionsupporting
confidence: 88%
“…The overall age-specific incidence patterns reported in this study were consistent with those reported in Western countries,2,3,1220 showing that OS and ES are more likely to be diagnosed in youth, whereas CS and GCT occur more frequently in middle-aged and elderly individuals, and chordomas and ameloblastomas predominantly affect elderly patients. However, more details remain to be clarified.…”
Section: Discussionsupporting
confidence: 88%
“…Primary chordomas are slow-growing, locally destructive, rare bone tumors arising from notochord tissue along the cranial-spinal axis [6,7,8,9]. Proximity to the brainstem, cranial nerves, and major intracranial vessels make this histologically low-grade neoplasm clinically malignant [7].…”
Section: Discussionmentioning
confidence: 99%
“…The overall incidence is reported to be 8.4 per ten million, with a higher incidence in males and individuals older than 40 years. 11,16 Tumors are reported to arise in the cranium (frequently clival, 32%), spine (33%) and sacrum (29%). 11,16 Chordomas are typically lobulated with fibrous trabeculae, and the presence of numerous vacuolated (physaliphorous) cells is characteristic.…”
Section: Introductionmentioning
confidence: 99%
“…11,16 Tumors are reported to arise in the cranium (frequently clival, 32%), spine (33%) and sacrum (29%). 11,16 Chordomas are typically lobulated with fibrous trabeculae, and the presence of numerous vacuolated (physaliphorous) cells is characteristic. 12 Although they infrequently metastasize, tumors are typically locally invasive with frequent recurrence, often owing to the difficulty of complete resection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation